2009
DOI: 10.1007/s00442-009-1451-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate diets derived from trophically transmitted fish parasites in the Bothnian Bay

Abstract: Parasites that are transmitted through predator-prey interactions may be used as indicators of trophic relationships between organisms. Yet, they are rarely used as such in the construction of topological (predator-prey) food webs. We constructed food webs of vertebrate trophic interactions using observed diet alone, trophically transmitted parasites alone, and the combination of the two based on data from 31 species of fish from the Bothnian Bay, Finland. The fish food web contained 530 links derived from obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 56 publications
2
68
0
Order By: Relevance
“…Valtonen et al, 2010). Brown et al (2001) proposed that complex cycles evolved Step 2: the flexible two-host cycle, where the parasite is optimized to host i, but can also survive and reproduce in host j.…”
Section: Enhanced Rate Of Sexual Encounter and Genotype Mixingmentioning
confidence: 99%
“…Valtonen et al, 2010). Brown et al (2001) proposed that complex cycles evolved Step 2: the flexible two-host cycle, where the parasite is optimized to host i, but can also survive and reproduce in host j.…”
Section: Enhanced Rate Of Sexual Encounter and Genotype Mixingmentioning
confidence: 99%
“…Variation in biotic factors, such as the foraging behavior of fish hosts in novel habitats, could possibly affect introduced parasite populations. Fish foraging behavior is linked to the host's acquisition of trophically transmitted parasites (Klimpel et al 2003;Knudsen et al 2004;Valtonen et al 2010;Locke et al 2014) and could therefore be a potential factor controlling the abundance of trophically transmitted parasites.…”
Section: Introductionmentioning
confidence: 99%
“…The role of feeding behaviour on the occurrence of parasitism in fish is well documented in the literature. The role of foraging behaviour, for example, has been reported as an important determinant of parasite communities (Knudsen et al 2004;Valtonen et al 2010). The feeding behaviour of different species of genus Schizothorax, which have been studies in past, revealed that these fishes are herbivores, and their diet is mainly composed of phytoplankton and rest contained aquatic invertebrates (Jan and Das, 1970).…”
Section: Variation Of a Oreini Infection Among Three Native Fish Spementioning
confidence: 99%